Comparative Analysis of Overheating Prevention and Stagnation Handling Measures for Photovoltaic-thermal (PV-T) Systems - Magalhães, Pedro M. L. P. (2018)
The stagnation temperatures experienced by glazed photovoltaic-thermal (PV-T) collectors pose a threat to their performance and longevity, in part due to the limited temperature stability of ethylene vinyl acetate (EVA) encapsulants. In order to identify suitable solutions for application in residential solar domestic hot water (SDHW) PV-T systems, a comparative analysis of known overheating prevention and stagnation handling measures was conducted and dynamic simulations were used to support the analysis. While no measure was found to comply with all desirable goals including reliability, implementation and operation costs, integral venting mechanisms were identified as the most promising among the control systems reviewed. Moreover, active collector heat dumping and automatic collector shading led to minimal electrical efficiency increases and decreases, respectively, while purging tank water when the collector overheats was found to be ineffective due to delays in the start of circulation.